Optimal Placement and Sizing of Reactive Power Compensation Devices in Power Grids with High Penetration of Distributed Generation - Feng, Nan; Niu, Tao; Yan, Jun; Zhang, Yufan; Feng, Yuyao; Lei, Yuli (Processes, 2025)
To address voltage stability challenges in power grids with high penetration of distributed generation (DG), this paper proposes an optimal configuration method for reactive power compensation devices. Voltage-weak nodes are first identified using a novel short-circuit ratio (SCR) index. An average electrical distance metric is then introduced to determine optimal installation nodes by computing distances between candidate nodes and weak nodes. Subject to constraints on maximum compensation capacity and allowable DG disconnection limits, MATLAB simulations validate the optimal configuration. Case studies on modified IEEE 9, 14 and 39 bus systems confirm the method’s efficacy: DG tripping due to low-/high-voltage ride-through failures is effectively mitigated, with minimum fault voltage increasing by 0.05–0.08 p.u. and voltage recovery time reduced by 0.15–0.8 s.